Phenetic Study of Tabernaemontana divaricata (L.) R.Br. ex Roem. & Schult. in Thailand - Nuchthongmuang, Wilaiwan; Petchsri, Sahanat; Boonkerd, Thaweesakdi; Sripinyowanich, Siriporn; Jongjitvimol, Touchkanin (HAYATI Journal of Biosciences, 2026)
Pinwheel Jasmine (Tabernaemontana divaricata L.; Apocynaceae) is widely distributed across South Asia, Thailand, and southern China and exhibits substantial morphological variation. This variability has resulted in persistent taxonomic confusion, particularly in Thailand, where distinguishing among phenotypic forms and related taxa remains challenging. Accurate taxonomic delimitation is essential for botanical classification, horticultural applications, conservation, and the reliable identification of plant resources. This study examined the taxonomic status of Pinwheel Jasmine in Thailand using numerical taxonomic approaches, including cluster and discriminant analyses. A total of 40 morphological characters (20 quantitative and 20 qualitative) were assessed across 210 operational taxonomic units (OTUs) representing seven phenotypes. Both analyses consistently resolved the OTUs into two distinct groups: (1) T. divaricata ‘Ceylon Jasmine’ (Phud Supachok) and (2) other Pinwheel Jasmine forms. Five quantitative characters were identified as the most diagnostic: lamina length (LML), lamina width (LMW), corolla lobe length (CLL), distance from the corolla tube base to stamen attachment (DCS), and style length (STL). These traits exhibited exceptionally high F-values in K-means cluster analysis (404.11, 432.90, 327.54, 530.04, and 181.02, respectively; p<0.01), indicating strong discriminatory power. The results demonstrate that Phud Supachok is consistently and clearly morphologically distinct from other Pinwheel Jasmine forms. However, because this study is based solely on phenetic data, additional molecular evidence is required before definitive taxonomic conclusions can be made. Integrative studies combining molecular and morphological data are recommended to refine species delimitation within Tabernaemontana.